Region of origin and consumers' quality perception of wine: An assimilation-contrast approach - Carla Ferreira; Lina Lourenço-Gomes; Lígia M. Costa Pinto (Wine Economics and Policy, 2021)
Wine quality perception involves both intrinsic and extrinsic attributes and is related to consumer liking and acceptability of a product. The main purpose of this paper is to evaluate the actual role of the region of origin cue on the experienced, expected, and perceived quality of wine, as well as on the discrepancies between them. Using an experimental design set up, real tasting sessions were applied to elicit consumer quality perception in three different information conditions: (1) blind tasting (2) labelled tasting (region informed evaluation); and (3) wine tasting under full information. In total, 136 wine consumers stated their preferences through liking score. The results from the assimilation-contrast framework show that region of origin affects the experienced, expected, and perceived quality, as well as the agreement between them. Thus, the region of origin may offer a good predictive value of the product, increasing the consumer expectations. These results have important implications for producers as they demonstrate that the region of origin may be used as a brand.
Keywords: 330; Assimilation-Contrast Approach; product quality; region of origin; wine